Producción a escala laboratorio de xilitol a partir de la semilla de tamarindo por medio fermentativo con Candida Tropicalis y Candida Guillermondii (2024)
"This research project initially aimed to compare two yeasts, Candida Tropicalis and Candida Guillermondii, for the production of xylitol from tamarind seeds. Which, due to availability reasons, ends up being a comparison between the yeasts Candida Tropicalis and Saccharomyces Cerevisiae, corresponding to a laboratory-scale study, in which an acid hydrolysis is used to break the bonds of glucose with D-xylose from the seed in order to obtain D-xylose as the product of interest and subsequently ferment it with the aforementioned yeasts to determine which one achieves a higher production of this organic sugar. The study variable was focused on two parts, the first corresponding to the amount of D-xylose obtained in the hydrolysis process and the second to the amount of xylitol produced in the comparison between yeasts during the fermentation process. In the second part of the process, the results were quantified using the liquid chromatography (HPLC) method, showing that the yeast Saccharomyces cerevisiae achieved a higher xylitol production at 72 hours of 1.629 g/L for a particle size of 0.381 mm, while the yeast Candida Tropicalis achieved a xylitol production of 0.627 g/L for the same particle size. The experimental design was based on taking the yeast to be used as the independent variable and the time it takes to carry out the fermentation of D-xylose as the dependent variable, which corresponds to a time of 24 and 72 hours, thus aiming to demonstrate and verify according to the time what the concentration of xylitol produced will be. The data obtained during this practice were processed through an ANOVA. Finally, for this project, a semi-industrial scale-up was carried out, in which a raw material flow of 70 kg/h was proposed, and it was found that the final mass converted into xylitol was 11.827 kg/h per hour."